IrRu / TiOxNy nanobelt composite catalyst and preparation method thereof
By using ethylene glycol reduction method to load the IrRu alloy on the titanium-containing nanoribbon and forming the IrRu/TiOxNy nanoribbon composite catalyst, the problems of high energy consumption and insufficient performance in the prior art are solved, and efficient and stable catalytic activity are achieved. Low loading IrRu alloy catalyst.
Patent Information
- Application Number
- CN202411535010.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art has problems such as high energy consumption when preparing IrRu alloy catalysts, inability to ensure the complete conversion of TiO2 into TiOxNy, insufficient research on the performance of IrRu alloy catalysts, and difficulty in improving the support.
The IrRu alloy was loaded on the titanium-containing nanoribbon by ethylene glycol reduction method to form an IrRu/TiOxNy nanoribbon composite catalyst, and the support nitriding temperature was reduced by nitriding treatment.
High catalytic activity and stability of low-loaded IrRu alloys are achieved, reducing the support nitriding temperature, and improving the specific surface area and reactive sites of the catalyst.
Smart Images

Figure CN119386915A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of catalyst preparation, and in particular relates to an IrRu / TiO x N y Nanobelt composite catalyst and preparation method thereof. Background Art
[0002] Hydrogen has become a versatile and efficient energy carrier in the green economy plan due to its high energy density, zero carbon emissions, and convenient storage and safe transportation after conversion into liquid fuel. However, the current mainstream methods, such as methane reforming, coal gasification or biomass conversion, all have the problem of large energy consumption and carbon dioxide emissions. In order to meet the carbon-free standard, its production should adopt cleaner processes, such as water electrolysis to produce hydrogen, especially water electrolysis coupled with renewable energy. Among them, the acidic proton-exchange membrane water electrolyser (PEMWE) has the advantages of higher voltage efficiency, lower ohmic loss, more compact system design, shorter start-up time, higher power density and current density, fewer side reactions and lower gas crossover, and can better adapt to the volatility of intermittent solar and wind energy for perfect linkage. It has attracted widespread attention from academia and industry and is considered to be the cornerstone of the future hydrogen economy. In order to improve the overall efficiency of hydrogen production from water electrolysis in PEMWE, electrocatalysts need to be used at the anode and cathode to accelerate the reaction kinetics, especially the anodic oxygen evolution reaction (OER) with four-electron transfer.
[0003] The order of OER activity of noble metal catalysts in acidic media is ruthenium (Ru) > iridium (Ir) > rhodium (Rh) > palladium (Pd) > platinum (Pt) > gold (Au), and the order of stability is Pt > Rh > Ir > Au > Ru. Therefore, IrRu alloy catalysts are currently considered to be the most promising acidic OER catalysts. However, metal Ir is one of the most scarce elements, which greatly limits its large-scale application. Studies have shown that the introduction of carriers can not only effectively improve the dispersion of metal nanoparticles and increase the number of active sites; it can also regulate their electronic structure and stability through strong interactions with metal nanoparticles, and ultimately reduce the amount of noble metals used. As a carrier for acidic OER catalysts, it must have the following characteristics: (1) sufficient conductivity to facilitate rapid electron transfer; (2) sufficient antioxidant and corrosion resistance to ensure the chemical stability of the electrode; (3) strong binding force with the metal catalyst to prevent the active component from falling off during the reaction. However, the commonly used carbon carriers (activated carbon, graphene, etc.) and TiN carriers with excellent conductivity will undergo oxidation reactions during the reaction, resulting in electrode instability, affecting the long-term use of the catalyst. In addition, the cost of graphene and TiN is relatively high, which will increase the cost of commercialization of PEMWE equipment to a certain extent. On the contrary, when titanium dioxide (TiO2), which has excellent stability in acidic and oxidizing environments, is used as a carrier, its extremely low conductivity cannot guarantee the effective transfer of electrons during the electrocatalytic reaction. Although increasing the Ir loading can improve the conductivity of TiO2, it will undoubtedly further increase the application cost.
[0004] In this context, researchers (M. Bele, P. Jovanovic, Z. Marinko, S. Drev, V. S. Selih, J. Kovac, M. Gaberscek, G. Koderman Podborsek, G. Drazic, N. Hodnik, A. Kokalj, L. Suhadolnik, ACS Catal. 2020, 10, 13688-13700) proposed another method to improve the conductivity of TiO2, that is, by converting TiO2 into TiN and forming TiO x N y The material has both the conductivity of TiN and the stability of TiO2. In addition, the calculation results show that the strong interaction between Ir and N ions in the carrier can increase the diffusion barrier and reduce the agglomeration of Ir nanoparticles. Finally, Ir / TiO x N y The OER activity of Ir / C is significantly higher than that of commercial IrO2.
[0005] However, in order to ensure the effective decomposition of ammonia into hydrogen and nitrogen, most of the preparation of TiO xN y The methods are to heat treat commercial P25 powder in an ammonia atmosphere at 800-900℃. x N y Most of the precious metal catalysts supported by the carrier are Ir, and due to the TiO x N y The specific surface area of the particles is small, and the effect is not good when they are loaded using the ethylene glycol reduction method.
[0006] That is, the catalysts prepared based on the existing carriers for loading IrRu alloys still have the following problems:
[0007] (1) TiO2 to TiO x N y The heat treatment temperature of the conversion is high, the reaction time is long, and the energy consumption is high;
[0008] (2) It is impossible to ensure that TiO2 will turn to TiO x N y Complete transformation of
[0009] (3) As a more promising IrRu alloy catalyst, it is supported on TiO x N y There are few studies on performance after carriers;
[0010] (4) How to effectively improve the carrier to enhance the effectiveness of the ethylene glycol reduction loading method.
[0011] Based on this, a new type of catalyst carrier for loading IrRu alloy and a preparation method thereof are now studied to solve the problems existing in the above-mentioned existing technologies. Summary of the invention
[0012] Purpose of the invention: The technical problem to be solved by the present invention is to provide a new type of IrRu alloy / carrier composite catalyst, so as to effectively solve the technical problems existing in the above prior art.
[0013] Technical solution: The method for preparing IrRu / TiOxNy nanobelt composite catalyst of the present invention comprises the following steps:
[0014] (1) adding iridium chloride and ruthenium chloride to ethylene glycol, stirring at room temperature for 30-60 minutes to obtain a mixed solution;
[0015] (2) adding the titanium nanobelt carrier to the mixed solution, and stirring the mixture under ultrasonication for 1-2 hours to obtain a uniformly dispersed solution;
[0016] (3) reacting the above solution at 150-180° C. for 2-5 hours, centrifuging, washing, and vacuum drying to obtain IrRu / titanium-containing nanobelt catalyst powder;
[0017] (4) IrRu / TiO nanobelt catalyst powder was placed in the middle of a tube furnace as a raw material, NH3 was introduced after vacuuming, and heated to 500-600°C under flowing NH3, kept warm for 1-5h, and then cooled to room temperature to obtain IrRu / TiO x N y Nanoribbon composite catalysts.
[0018] When preparing the IrRu / titanium-containing nanobelt composite catalyst, the IrRu alloy is first loaded on the titanium-containing nanobelt based on the ethylene glycol reduction method to obtain the IrRu / titanium-containing nanobelt. The IrRu / titanium-containing nanobelt is used as a carrier precursor, and the ultra-high specific surface area and abundant reactive sites can be used to effectively shorten the nitridation time; it can also be used as a catalyst to generate high reactivity in the NH3 decomposition process, activate ammonia molecules at a lower temperature, show stable ammonia decomposition activity, and effectively reduce the nitridation temperature; and the finally prepared IrRu / TiO x N y The nanobelt composite catalyst can not only achieve excellent catalytic activity and stability based on a low loading of IrRu alloy (loading is only 10-30wt%), but also significantly reduce the carrier nitridation temperature.
[0019] Furthermore, in step (1) of the preparation method of the present invention, the molar ratio of Ir / Ru in the iridium chloride and ruthenium chloride is (1:9)-(9:1).
[0020] Furthermore, in step (1) of the preparation method of the present invention, the mass of the ethylene glycol is 20-40 times the total mass of the iridium chloride and the ruthenium chloride.
[0021] Furthermore, in step (2) of the preparation method of the present invention, the titanium-containing nanobelt is a hydrogen titanate nanobelt, a rutile TiO2 nanobelt, anatase TiO2 nanobelt or a brookite TiO2 nanobelt.
[0022] Furthermore, in step (2) of the preparation method of the present invention, the added mass of the titanium-containing nanobelts is 7 / 3 to 9 times the total mass of the metals in the added iridium chloride and ruthenium chloride.
[0023] Furthermore, in step (4) of the preparation method of the present invention, the gas flow rate of NH3 is 15-30 mL / min.
[0024] IrRu / TiO x N y The nanobelt composite catalyst is prepared by the above preparation method, and comprises TiO x N yA nanobelt carrier and an IrRu alloy loaded on the carrier, wherein the loading amount of the IrRu alloy is 10-30wt%; wherein x+y=1, 0≤x≤1, 0≤y≤1.
[0025] Furthermore, the IrRu / TiO x N y The molar ratio of Ir to Ru in the IrRu alloy of the nanobelt composite catalyst is (1:9)-(9:1).
[0026] Beneficial effects: Compared with the prior art, the significant advantages of the present invention are: the IrRu alloy acidic electrolysis water oxygen evolution catalyst of the present invention is based on TiO x N y Based on the nanobelt carrier, a low loading of IrRu alloy (loading is only 10-30wt%) can be achieved while still having excellent catalytic activity and stability. 2 At a current density of 2.5V, the overpotential is 250-272mV; at a scan rate of 100mV / s, the overpotential is 0.05-1.0V RHE After 20,000 cycles, 10 mA / cm 2 The overpotential increases by 3-19mV at a current density of . BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The IrRu / TiO prepared in Example 1 of the present invention x N y XRD patterns of the nanobelt composite catalyst and P25 after the same nitridation treatment;
[0028] Figure 2 The IrRu / TiO prepared in Example 1 of the present invention x N y SEM image of nanobelt composite catalyst;
[0029] Figure 3 In order to utilize the IrRu / TiO prepared in Example 1 of the present invention x N y TEM image of nanobelt composite catalyst;
[0030] Figure 4 In order to utilize the IrRu / TiO prepared in Example 1 of the present invention x N y LSV curves of OER of nanobelt composite catalyst and commercial IrO2 catalyst;
[0031] Figure 5 In order to utilize the IrRu / TiO prepared in Example 1 of the present invention x Ny Stability testing of nanobelt composite catalysts and commercial IrO2 catalysts for OER. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0033] It should be noted that the raw materials used in the present invention contain titanium nanobelts, which are hydrogen titanate nanobelts, rutile TiO2 nanobelts, anatase TiO2 nanobelts and brookite TiO2 nanobelts, all of which are synthesized according to existing literature. Other raw materials can be purchased from the market, wherein the purity of NH3 is 99.9%; the purity of iridium chloride is ≥99.8%; and the purity of ruthenium chloride is ≥99.8%.
[0034] Example 1
[0035] The IrRu alloy acidic water electrolysis oxygen evolution catalyst of Example 1 includes TiO x N y Nanobelt carrier and TiO x N y The IrRu alloy on the nanobelt carrier has a loading amount of 15 wt % and a molar ratio of Ir to Ru of 1:3. The IrRu alloy is prepared by the following steps:
[0036] (1) adding a certain mass of iridium chloride and ruthenium chloride (Ir / Ru molar ratio is 1:3) to a certain mass of ethylene glycol (25 times the total mass of iridium chloride and ruthenium chloride), and stirring at room temperature for 50 minutes;
[0037] (2) adding a certain mass of hydrogen titanate nanoribbons (17 / 3 times the total mass of metals in iridium chloride and ruthenium chloride, i.e., 15 wt% of precious metal loading) to the above solution and stirring under ultrasound for 1 h;
[0038] (3) reacting the uniformly dispersed solution in an oil bath at 160° C. for 3 h, centrifuging at 18300 g, washing, and vacuum drying at 120° C. to obtain IrRu / hydrogen titanate nanobelt catalyst powder;
[0039] (4) IrRu / hydrogen titanate nanobelts were placed in the middle of a tube furnace as raw materials, NH3 was introduced at a gas flow rate of 15 mL / min after vacuuming, and heated to 600°C at a heating rate of 6°C / min, kept warm for 2 h, and cooled to room temperature to obtain IrRu / TiO x N y Nanoribbon composite catalyst powder.
[0040] Composition Characterization 1-TiO x N y Nanoribbon carrier
[0041] Figure 1 The XRD patterns of the IrRu / hydrogen titanate nanobelts prepared in Example 1 of the present invention and P25 after the same nitridation treatment. Figure 1 It can be seen that the IrRu / TiO prepared by IrRu / hydrogen titanate nanobelts x N y The nanoribbons only show TiO x N y The characteristic peaks of the (111), (200), (220) and (311) crystal planes of the IrRu / TiO2 phase and the characteristic peaks of the (100), (002), (101), (102) and (110) crystal planes of the Ir1Ru3 phase are weak, indicating that the IrRu / TiO2 phase is no longer present. However, after the commercial P25 is nitrided at the same time and temperature, the TiO2 phase still remains. This indicates that the preparation of IrRu / TiO2 x N y The nitridation temperature of the nanobelts was significantly reduced and the time was significantly shortened. x N y The N content of the carrier was 10.06%.
[0042] Structural characterization of 2-TiO x N y Nanoribbon carrier
[0043] Figure 2 The IrRu / TiO prepared in Example 1 of the present invention x N y SEM photo of nanobelts. As can be seen from the figure, after nitridation, the ribbon structure of hydrogen titanate nanobelts can be effectively retained. In addition, the surface area test results and the Brunauer-Emmett-Teller (BET) method show that the TiO x N y The specific surface area of the nanobelt carrier is 43.85 m 2 g -1 , which is significantly higher than that of P25 after the same nitridation treatment (18.35m 2 g -1 ).
[0044] Structural characterization 3-IrRu / TiO x N y Nanoribbon Catalysts
[0045] Figure 3 In order to utilize the IrRu / TiO prepared in Example 1 of the present invention x N yTEM photo of the nanobelt catalyst. As can be seen from the figure, the particle size of the IrRu alloy prepared using ethylene glycol is about 3-5nm and is evenly dispersed on the carrier.
[0046] Performance Test 1- Conductivity
[0047] The IrRu / TiO prepared in Example 1 was tested by a four-terminal powder resistivity tester. x N y The conductivity of the nanobelt composite catalyst was tested, and the results showed that the conductivity was 34S / cm under a pressure of 30MPa.
[0048] Performance test 2-catalytic activity and stability
[0049] The IrRu / TiO prepared in Example 1 x N y The nanobelt composite catalyst was tested for OER catalytic activity and stability. When evaluating the OER stability, the scanning rate was 100 mV / s at 0.05-1.0 V. RHE The catalyst overpotentials before and after the cycles were compared. Figure 4 and Figure 5 As shown. Figure 4 It can be seen that at 10mA / cm 2 At a current density of 1.5 volts, the overpotential is 250 mV, which is significantly better than commercial IrO2 (339 mV) at the same loading. At a scan rate of 100 mV / s, the overpotential is 0.05-1.0 V. RHE After 20,000 cycles, 10 mA / cm 2 The overpotential at the current density is increased by 3mV, which is significantly better than commercial IrO2 (37mV).
[0050] Example 2
[0051] The IrRu alloy acidic water electrolysis oxygen evolution catalyst of Example 2 includes TiO x N y Nanobelt carrier and TiO x N y The IrRu alloy on the nanobelt carrier has a loading amount of 30 wt % and a molar ratio of Ir to Ru of 1:4. The IrRu alloy is prepared by the following steps:
[0052] (1) adding a certain mass of iridium chloride and ruthenium chloride (Ir / Ru molar ratio is 1:4) into a certain mass of ethylene glycol (30 times the total mass of iridium chloride and ruthenium chloride), and stirring at room temperature for 50 min;
[0053] (2) adding a certain mass of hydrogen titanate nanoribbons (7 / 3 times the total mass of metals in iridium chloride and ruthenium chloride, i.e., 30 wt% of precious metal loading) to the above solution and stirring under ultrasound for 1 h;
[0054] (3) reacting the uniformly dispersed solution in an oil bath at 180° C. for 4 h, centrifuging at 18300 g, washing, and vacuum drying at 120° C. to obtain IrRu / hydrogen titanate nanobelt catalyst powder;
[0055] (4) IrRu / hydrogen titanate nanobelts were placed in the middle of a tube furnace as raw materials, NH3 was introduced at a gas flow rate of 20 mL / min after vacuuming, and heated to 600°C at a heating rate of 6°C / min, kept warm for 3 h, and cooled to room temperature to obtain IrRu / TiO x N y Nanoribbon composite catalyst powder.
[0056] Performance Testing
[0057] The IrRu / TiO prepared in this example x N y The nanobelt composite catalyst was tested and only TiO x N y The characteristic peaks of (111), (200), (220) and (311) crystal planes and the weak characteristic peaks of (100), (002), (101), (102) and (110) crystal planes of metal Ir1Ru4 are shown. The nitrogen content is 12.33% and the specific surface area is 29.85m 2 g -1 , the conductivity is 40S / cm@30MPa; at 10mA / cm 2 At a current density of 1.5, the overpotential is 261 mV; at a scan rate of 100 mV / s, the overpotential is 0.05-1.0 V. RHE After 20,000 cycles, 10 mA / cm 2 The overpotential increases by 12 mV at a current density of .
[0058] Example 3
[0059] The IrRu alloy acidic water electrolysis oxygen evolution catalyst of Example 3 includes TiO x N y Nanobelt carrier and TiO x N y The IrRu alloy on the nanobelt carrier has a loading amount of 25 wt % and a molar ratio of Ir to Ru of 1:8. It is prepared by the following steps:
[0060] (1) adding a certain mass of iridium chloride and ruthenium chloride (Ir / Ru molar ratio is 1:8) to a certain mass of ethylene glycol (30 times the total mass of iridium chloride and ruthenium chloride), and stirring at room temperature for 60 minutes;
[0061] (2) adding a certain mass of anatase TiO2 nanobelts (3 times the total mass of metals in iridium chloride and ruthenium chloride, i.e., 25 wt% noble metal loading) to the above solution and stirring under ultrasound for 1 h;
[0062] (3) reacting the uniformly dispersed solution in an oil bath at 180° C. for 5 h, centrifuging at 18,300 g, washing, and vacuum drying at 120° C. to obtain IrRu / anatase TiO2 nanobelt catalyst powder;
[0063] (4) IrRu / anatase TiO2 nanobelts were placed in the middle of a tube furnace as raw materials, NH3 was introduced at a gas flow rate of 30 mL / min after vacuuming, and heated to 500°C at a heating rate of 8°C / min, kept at this temperature for 5 h, and cooled to room temperature to obtain IrRu / TiO x N y Nanoribbon composite catalyst powder.
[0064] Performance Testing
[0065] The IrRu / TiO prepared in this example x N y The nanobelt composite catalyst was tested and only TiO x N y The characteristic peaks of (111), (200), (220) and (311) crystal planes and the weak characteristic peaks of (100), (002), (101), (102) and (110) crystal planes of metal Ir1Ru3 are shown in Figure 2. The nitrogen content is 9.67% and the specific surface area is 50.74 m 2 g -1 , conductivity is 27S / cm@30MPa; IrRu / TiO x N y Nanobelt catalyst at 10 mA / cm 2 At a current density of 1.5, the overpotential is 258 mV; at a scan rate of 100 mV / s, the overpotential is 0.05-1.0 V. RHE After 20,000 cycles, 10 mA / cm 2 The overpotential increases by 19 mV at a current density of .
[0066] Example 4
[0067] The IrRu alloy acidic water electrolysis oxygen evolution catalyst of Example 4 includes TiO x N yNanobelt carrier and TiO x N y The IrRu alloy on the nanobelt carrier has a loading amount of 15 wt % and a molar ratio of Ir to Ru of 1:1. The IrRu alloy is prepared by the following steps:
[0068] (1) adding a certain mass of iridium chloride and ruthenium chloride (Ir / Ru molar ratio is 1:1) to a certain mass of ethylene glycol (40 times the total mass of iridium chloride and ruthenium chloride), and stirring at room temperature for 50 minutes;
[0069] (2) adding a certain mass of rutile TiO2 nanobelts (17 / 3 times the total mass of metals in iridium chloride and ruthenium chloride, i.e., 15 wt% of precious metal loading) to the above solution and stirring under ultrasound for 1 h;
[0070] (3) reacting the uniformly dispersed solution in an oil bath at 180° C. for 4 h, centrifuging at 18,300 g, washing, and vacuum drying at 120° C. to obtain IrRu / rutile TiO2 nanobelt catalyst powder;
[0071] (4) IrRu / rutile TiO2 nanobelts were placed in the middle of a tube furnace as raw materials. After evacuation, NH3 was introduced at a gas flow rate of 30 mL / min and heated to 600°C at a heating rate of 8°C / min. The temperature was kept for 3 h and cooled to room temperature. x N y Nanoribbon composite catalyst powder.
[0072] Performance Testing
[0073] The IrRu / TiO prepared in this example x N y The nanobelt composite catalyst was tested and only TiO x N y The characteristic peaks of (111), (200), (220) and (311) crystal planes and the weak characteristic peaks of (100), (002), (101), (102) and (110) crystal planes of metal IrRu are shown in Figure 2. The nitrogen content is 13.88% and the specific surface area is 28.74 m 2 g -1 , the conductivity is 42S / cm@30MPa; IrRu / TiO x N y Nanobelt catalyst at 10 mA / cm 2 At a current density of 1.5, the overpotential is 272 mV; at a scan rate of 100 mV / s, the overpotential is 0.05-1.0 V. RHE After 20,000 cycles, 10 mA / cm 2The overpotential increases by 8 mV at a current density of .
[0074] In addition to the above embodiments, the present invention also provides IrRu / TiO x N y The molar ratio of Ir to Ru in the nanobelt composite catalyst is in the range of (1:9)-(9:1), the IrRu alloy loading is in the range of 10-30wt%, and the process reaction conditions for preparation all have excellent OER catalytic activity and stability. Therefore, the embodiment part is not verified separately.
Claims
1. Preparation of IrRu / TiO x N y The method of nanobelt composite catalyst is characterized in that The steps include: (1) adding iridium chloride and ruthenium chloride to ethylene glycol, stirring at room temperature for 30-60 minutes to obtain a mixed solution; (2) adding the titanium nanobelt carrier to the mixed solution, and stirring the mixture under ultrasonication for 1-2 hours to obtain a uniformly dispersed solution; (3) reacting the above solution at 150-180° C. for 2-5 hours, centrifuging, washing, and vacuum drying to obtain IrRu / titanium-containing nanobelt composite catalyst powder; (4) IrRu / titanium-containing nanobelt composite catalyst powder is placed in the middle of a tube furnace as a raw material, NH3 is introduced after vacuuming, and heated to 500-600°C under flowing NH3, kept warm for 1-5h, and then cooled to room temperature to obtain IrRu / TiO x N y Nanoribbon composite catalysts.
2. Preparation of IrRu / TiO according to claim 1 x N y The method of nanobelt composite catalyst is characterized in that In step (1), the molar ratio of Ir / Ru in the iridium chloride and ruthenium chloride is (1:9)-(9:1).
3. Preparation of IrRu / TiO according to claim 1 x N y The method of nanobelt composite catalyst is characterized in that In step (1), the mass of the ethylene glycol is 20-40 times the total mass of the iridium chloride and the ruthenium chloride.
4. Preparation of IrRu / TiO according to claim 1 x N y The method of nanobelt composite catalyst is characterized in that In step (2), the titanium-containing nanobelt is a hydrogen titanate nanobelt, a rutile TiO2 nanobelt, anatase TiO2 nanobelt or a brookite TiO2 nanobelt.
5. Preparation of IrRu / TiO according to claim 1 x N y The method of nanobelt composite catalyst is characterized in that In step (2), the amount of the titanium-containing nanobelt added is 7 / 3-9 times the total mass of the metals in the added iridium chloride and ruthenium chloride.
6. Preparation of IrRu / TiO according to claim 1 x N y The method of nanobelt composite catalyst is characterized in that In step (4), the gas flow rate of NH3 is 15-30 mL / min.
7. An IrRu / TiOxNy nanobelt composite catalyst, characterized in that: The catalyst is prepared by the preparation method according to claim 1, and comprises TiO x N y A nanobelt carrier and an IrRu alloy loaded on the carrier, wherein the loading amount of the IrRu alloy is 10-30wt%; wherein x+y=1, 0≤x≤1, 0≤y≤1.
8. IrRu / TiO according to claim 7 x N y A nanobelt composite catalyst, characterized in that: In the IrRu alloy, the molar ratio of Ir to Ru is (1:9)-(9:1).
Citation Information
Cited By
Preparation method and application of IrRu / TiON acidic oxygen evolution reaction electrocatalyst
CN122543093A
Preparation method and application of irru / tion acidic oxygen evolution reaction electrocatalyst
CN122543093B